2010
DOI: 10.2465/jmps.090817
|View full text |Cite
|
Sign up to set email alerts
|

Sr-sulphate and associated minerals found from kyanite-bearing eclogite in the Moldanubian Zone of the Bohemian Massif, Czech Republic

Abstract: Sr -sulphate, celestine, was newly found in a kyanite -bearing eclogite associated with the Nové Dvory peridotite mass in the Moldanubian Zone of the Bohemian Massif, Czech Republic. Celestine is closely associated with anhydrite, pyrite, pyrrhotite and chalcopyrite, and those minerals occur in the matrix, where fine -grained omphacite aggregate and kelyphites after garnet develop. A common Sr reservoir in eclogite is known to be epidote, but the maximum pressure -temperature (P -T) conditions of the studied e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…The presence of celestine can be the mark of a redox environment (Hadji et al , 2019); however, anhydrite, celestine and analcime are rarely observed within borate deposits (Helvaci, 1995). Nakamura et al (2010) describe an occurrence from the Bohemian massif, Czech Republic of eclogite as a carrier of Sr-sulfate celestine.…”
Section: Overview Of Celestine-bearing Environmentsmentioning
confidence: 99%
“…The presence of celestine can be the mark of a redox environment (Hadji et al , 2019); however, anhydrite, celestine and analcime are rarely observed within borate deposits (Helvaci, 1995). Nakamura et al (2010) describe an occurrence from the Bohemian massif, Czech Republic of eclogite as a carrier of Sr-sulfate celestine.…”
Section: Overview Of Celestine-bearing Environmentsmentioning
confidence: 99%